KECENDERUNGAN KECURANGAN PADA ALOKASI DANA DESA: ANALISIS FRAUD DIAMOND DAN RELIGIUSITAS - Priyastiwi Priyastiwi; Hasanah Setyowati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study examines dimensions of fraud diamond against the intention of financial fraud in village fund allocation. Based on fraud diamond theory that is used in public organizations, especially in the management of village funds. This study also includes religiosity as a factor that can moderate the effect of pressure, opportunity, rationality and capability on fraudulent intentions in the Village Fund Allocation. The research sample is selected purposively: the Technical Implementer of Village Financial Management (PTPKD) or village officials responsible for managing village funds in the Special Region of Yogyakarta. The data collection technique using a questionnaire to answer the dimensions of the fraud diamond, namely pressure, opportunity, rationality, and capability, as well as the variables of religiosity and fraud intention. Based on the test results, pressure and weak internal control system had a positive and significant effect on the fraud intention. Meanwhile, religiosity harms fraud intention in village fund allocation. The results also show that religiosity reduces pressure and a weak internal control system intends to allocate village funds fraudulently. This study explains that the village-level government officer as an agent takes actions that want to benefit themselves, whilst they are given the authority to manage financial allocation given from the central government. This behaviour occurred because of pressure, opportunity, rationalization and capability. This research provides insights and ways to control fraudulent behaviour in village fund allocations when the factors that cause fraudulent intentions in village fund allocations are known. This study examines dimensions of fraud diamond against the intention of financial fraud in village fund allocation. Based on fraud diamond theory that is used in public organizations, especially in the management of village funds. This study also includes religiosity as a factor that can moderate the effect of pressure, opportunity, rationality and capability on fraudulent intentions in the Village Fund Allocation. The research sample is selected purposively: the Technical Implementer of Village Financial Management (PTPKD) or village officials responsible for managing village funds in the Special Region of Yogyakarta. The data collection technique using a questionnaire to answer the dimensions of the fraud diamond, namely pressure, opportunity, rationality, and capability, as well as the variables of religiosity and fraud intention. Based on the test results, pressure and weak internal control system had a positive and significant effect on the fraud intention. Meanwhile, religiosity harms fraud intention in village fund allocation. The results also show that religiosity reduces pressure and a weak internal control system intends to allocate village funds fraudulently. This study explains that the village-level government officer as an agent takes actions that want to benefit themselves, whilst they are given the authority to manage financial allocation given from the central government. This behaviour occurred because of pressure, opportunity, rationalization and capability. This research provides insights and ways to control fraudulent behaviour in village fund allocations when the factors that cause fraudulent intentions in village fund allocations are known.